Pelatihan Pembuatan Kitchen Garden di Desa Glagahwero Jember sebagai Upaya Menuju Desa Agroeduwisata : Training on the Production Plant Growth Promoting Rhizobacteria based on Bamboo Root for the Karangrejo-Jember Farmer as an environmental agricultural solution - Wilujeng, Elly Daru Ika; Adnan, Moch. Rosyadi; Rahmawati, Dwi; Ermawati, Netty; Maulinda, Restiana; Prasetyo, Hari (Politeknik Negeri Jember, 2025)
Located in Kalisat Subdistrict, Jember Regency, Glagahwero Village has abundant potential, encompassing water rafting adventures, smart green house structures, and the appealing